Guest Expectations vs. Hotel Performance: a study of Guest Satisfaction in Uttarakhand's Hill Destination (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Nainital, known as the Lake District of Uttarakhand, is a well-liked hill station in North Indiathat has been a favorite of foreign visitors ever since the British colonial era. Nainital has an abundanceof hotels and other lodging options, from more modest hotels to five-star establishments, toaccommodate travelers staying in town for the night. A company's performance is directly tied to thenumber of satisfied and returning consumers they have. The major motivation for doing this survey wasto assess the level of contentment locals had with the range of lodging options in Nainital. The researchalso aims to categorize any relevant aspects that affect guests' experiences in Nainital's lodging sector.To accomplish the set goals of the study, primary data were collected from 200 tourists who visited thestudy area for a variety of reasons using structured questionnaires and random sampling techniques togather information on various service attributes related to the hospitality industry that can influencecustomer satisfaction. The findings provide light on how consumers in Nainital perceive the quality ofservices provided to them and on the broad elements that influence their attitudes about the hospitalitysector overall. The findings may be utilized as a road map for hotel managers to improve service qualityand bottom-line results by focusing on the most important quality indicators.